Vein morphometry in end-stage kidney disease: Teasing out the contribution of age, comorbidities, and vintage to chronic wall remodeling - Labissiere, Xochilt; Zigmond, Zachary M.; Challa, Akshara; Montoya, Christopher; Manzur-Pineda, Karen; Abraham, Amalia; Tabbara, Marwan; Salama, Alghidak; Pan, Yue; Salman, Loay H.; Yang, Xiaofeng; Vazquez-Padron, Roberto I.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Chronic kidney disease (CKD) is a highly comorbid condition with significant effects on vascular health and remodeling. Upper extremity veins are important in end-stage kidney disease (ESKD) due to their potential use to create vascular accesses. However, unlike arteries, the contribution of CKD-associated factors to the chronic remodeling of veins has been barely studied. Methods We measured morphometric parameters in 315 upper extremity veins, 131 (85% basilic) from stage 5 CKD/ESKD patients and 184 (89% basilic) from non-CKD organ donors. Associations of demographic and clinical characteristics with intimal hyperplasia (IH) and medial fibrosis were evaluated using multivariate regression models. Results The study cohort included 33% females, 30% blacks, 32% Hispanics, and 37% whites. Over 60% had hypertension, and 25% had diabetes independent of CKD status. Among kidney disease participants, 26% had stage 5 CKD, while 22 and 52% had ESKD with and without history of a previous arteriovenous fistula/graft (AVF/AVG), respectively. Intimal hyperplasia was associated with older age (β = 0.13 per year, confidence interval [CI] = 0.002–0.26), dialysis vintage > 12 months (β = 0.22, CI = 0.09–0.35), and previous AVF/AVG creation (β = 0.19, CI = 0.06–0.32). Upper quartile values of IH were significantly associated with diabetes (odds ratio [OR] = 2.02, CI = 1.08–3.80), which demonstrated an additive effect with previous AVF/AVG history and longer vintage in exacerbating IH. Medial fibrosis also increased as a function of age (β = 0.17, CI = 0.04–0.30) and among patients with diabetes (β = 0.15, CI = 0.03–0.28). Age was the predominant factor predicting upper quartile values of fibrosis (OR = 1.03 per year, CI = 1.01–1.05) independent of other comorbidities. Conclusion Age and diabetes are the most important risk factors for chronic development of venous IH and fibrosis independent of CKD status. Among kidney disease patients, longer dialysis vintage, and history of a previous AVF/AVG are strong predictors of IH.